Preparation and Characterization of Chitosan Nanoparticles for Chemotherapy of Melanoma Through Enhancing Tumor Penetration - Guo, Hui; Li, Faping; Qiu, Heping; Liu, Jianhua; Qin, Sihao; Hou, Yuchuan; Wang, Chunxi (Frontiers in Pharmacology, 2020)
The poor solubility and permeability of most chemotherapeutic drugs lead to unsatisfactory bioavailability combined with insufficient drug concentration. In this study, positively charged nanoparticles based on chitosan were developed and synthesized to enhance tumor penetration capability of 10-Hydroxycamptothecin (HCPT) in order to improve the chemotherapeutic effect of melanoma. The HCPT encapsulated nanoparticles were noted as NPs/HCPT. NPs/HCPT was characterized by dynamic light scattering and zeta potential measurements. In addition, cell uptake, in vitro cytotoxicity, apoptosis and in vivo antitumor activity of NPs/HCPT were further investigated. The average diameter of NPs/HCPT was approximately 114.6 ± 4.1 nm. The viability of murine melanoma cell lines (B16F10 and B16F1) was significantly decreased due to interaction with NPs/HCPT. Moreover, NPs/HCPT significantly inhibited the progression of tumors. These investigations implied that cationic NPs/HCPT could be potentially applied as a promising drug delivery nanosystem.